One way trip: advances and challenges in the protection of foreigners under refugees status and refugees claimants in Perú - Rebaza Vilchez, Karen Maribel (2016)
The article presents a summary analysis - from a human rights perspective – of the international obligations of the Peruvian State against the attendance of foreigners in search of the refugee recognition and those who already hold this international legal status.